2021
DOI: 10.1007/s13171-020-00238-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Designs for Model Averaging in non-nested Models

Abstract: In this paper we construct optimal designs for frequentist model averaging estimation. We derive the asymptotic distribution of the model averaging estimate with fixed weights in the case where the competing models are non-nested. A Bayesian optimal design minimizes an expectation of the asymptotic mean squared error of the model averaging estimate calculated with respect to a suitable prior distribution. We derive a necessary condition for the optimality of a given design with respect to this new criterion. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
1
Order By: Relevance
“…The performance of the proposed Machine Learning Model for 'Heterogeneous data & Weight Algorithm' is analysed with various classifiers. The statistical methods have revealed that penalized regression studies are being used to improve the predictions on outcomes by implementing model averaging [Alhorn et. al., (2021)] ideas.…”
Section: Model Estimations With Weighted Probabilitymentioning
confidence: 99%
“…The performance of the proposed Machine Learning Model for 'Heterogeneous data & Weight Algorithm' is analysed with various classifiers. The statistical methods have revealed that penalized regression studies are being used to improve the predictions on outcomes by implementing model averaging [Alhorn et. al., (2021)] ideas.…”
Section: Model Estimations With Weighted Probabilitymentioning
confidence: 99%
“…46) Eine weitere Möglichkeit, naturwissenschaftliche Inhalte im Unterricht über Spiele zu vermitteln (Gamification), sind Escape Rooms. [47][48][49][50] Auch in der chemiedidaktischen Forschung scheinen sie angekommen zu sein, so gibt es richten sich neu geförderte chemiedidaktische Teilprojekte in Sonderforschungsbereichen an Schulen, Schülerlabore und die Öffentlichkeit. Aktuelle Forschungsfelder sind hier etwa nachhaltige Energieversorgung, 55) künstliche Photosynthese, 56) Nanomedizin 57) oder Kompositmaterialien für die biomagnetische Diagnose.…”
Section: Digitalisierung Und Inklusionunclassified